The Impact of Emotional Intelligence on Clinical Adaptability of Nursing Interns under the "2+2" Teaching Model: The Moderating Role of Social Support - Shen, Yaojiong; Guo, Qiaoqiao; Sun, Hairou; Fang, Yunuo; Shou, Yinuo; Lin, Yuying (International Journal of Public Health and Medical Research, 2026)
Objective To investigate the clinical adaptation status of undergraduate nursing students under the "2+2" teaching model during their clinical clerkship, and to analyze the relationship with emotional intelligence and influencing factors. Methods A cross-sectional survey design was employed, involving 230 nursing interns under the "2+2" teaching model. Questionnaires including a General Information Questionnaire, the Maladaptive Behavior Scale, the Wong and Law Emotional Intelligence Scale (WLEIS), the Social Support Rating Scale, and the Chinese Big Five Personality Inventory were used for data collection. Statistical analysis was performed using SPSS 25.0, including descriptive analysis, univariate analysis, and multivariate Logistic regression analysis. Results The detection rate of poor clinical adaptation among nursing students was 57.8%. Univariate analysis showed that gender, dimensions of emotional intelligence, teaching support, and social support were significantly correlated with adaptability (P<0.05). Multivariate Logistic regression analysis indicated that "Use of Emotion" (OR=2.703) and "Regulation of Emotion" (OR=2.174) were independent predictive factors for clinical adaptability. Conclusion The problem of poor clinical adaptation among nursing students under the "2+2" model is prominent. The abilities of "Use of Emotion" and "Regulation of Emotion" in emotional intelligence, as well as the external support system, are key factors affecting their adaptability. It is suggested to enhance nursing students’ clinical adaptability by strengthening emotional intelligence training, optimizing teaching support, and building a supportive environment.